Empowering local tourism stakeholders: a muslim-friendly approach to sustainable geo-tourism in Langkawi’s UGGp - Saffinee, Siti Syahirah; Jamaludin, Mohammad Aizat (HH Publisher, 2023)
The halal tourism industry is growing rapidly and is estimated to reach a value of $300 billion by 2030. However, it is crucial that this growth is sustainable and respects the cultural and religious beliefs of the Muslim community. A qualitative study was conducted to examine the current practices of tourism stakeholders in Langkawi UNESCO Global Geopark (UGGp)regarding sustainability in Halal tourism. The study used ATLAS.ti to analyse interview transcriptions and identify current practices. The study’s findings provide recommendations for tourism stakeholders to promote sustainable tourism that aligns with Islamic values. It is essential for the government, private sector, local communities, and academia to collaborate to ensure that Muslim friendly tourism is developed as a brand in a way that benefits all stakeholders and the environment. This study highlights the importance of working together to achieve a sustainable Muslim friendly travel industry.